2020
DOI: 10.4081/idr.2020.8717
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitogen-Activated Protein Kinase Signaling Pathway and Proinflammatory Cytokines by Ursolic Acid in Murine Macrophages Infected with Mycobacterium avium

Abstract: Mycobacterium avium, one of the closest relatives of Mycobacterium tuberculosis (MTB), offers an advantage in studying MTB because of its tuberculosis-like effect in humans and host immune tolerance. This study examined the antimycobacterial action of ursolic acid and its regulation in macrophages during infection. Colony-forming units of the bacteria were determined in the cell lysate of macrophages and in the supernatant. The effect of ursolic acid on macrophages during infection was determined by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The UA drug was extracted from many plants such as the whole grass of the Labiatae plant, Prunella vulgaris, and the leaves of the holly, holly, iron holly leaves. 33 The UA is a triterpenoid compound found in natural plants and has many biological effects such as sedative, 34 anti-inflammatory, 35 antibacterial, 36 and immune defense responses. 37 The Ursolic acid (UA), also promote osteoblast differentiation and new bone formation.…”
Section: Resultsmentioning
confidence: 99%
“…The UA drug was extracted from many plants such as the whole grass of the Labiatae plant, Prunella vulgaris, and the leaves of the holly, holly, iron holly leaves. 33 The UA is a triterpenoid compound found in natural plants and has many biological effects such as sedative, 34 anti-inflammatory, 35 antibacterial, 36 and immune defense responses. 37 The Ursolic acid (UA), also promote osteoblast differentiation and new bone formation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to promote phagocytosis, autophagy induction, and ROS production in macrophages ( Figure 3 ). Previous studies have revealed that UA promotes the intracellular killing effect of macrophages in mycobacterial infection ( 164 166 , 192 , 193 ). UA treatment significantly reduced the lung Mtb burden and pneumonic lung area ( 164 ) ( Table 2 ).…”
Section: Hdts Modulate Macrophage Functions For Mac Infectionmentioning
confidence: 99%
“…activated protein kinase (p38MAPK) [32]. Therefore, UA could avert SARS-CoV-2 infection from causing ALI through modulation of proinflammatory and inflammatory signaling pathways.…”
Section: Effective For Treatment Of Multiple Sclerosis By Inhibiting Th17mentioning
confidence: 99%